English Language Anxiety among College Students - Louie Giray; Ma. Angelica Alcala; Jelomil Edem; Tracy Mauve Sabacajan (CV. Literasi Indonesia, 2022)
Most Filipinos spend their time learning the English language in schools, given the mandate of the government. Hence, English is used as a medium of instruction in many higher education institutions in the Philippines. Despite its prevalence, many Filipinos, including college students, are still anxious when utilizing it in communication. In research undertakings, little is being discussed about this type of language anxiety in the Philippine context. To bridge this research gap, the aim of this study, hence, is to explore the English language anxiety among Filipino college students in state universities and colleges in Metro Manila, Philippines. Data were obtained from 37 college students through purposive sampling. Then, the data were analyzed using thematic analysis. Four themes emerged, namely: (1) lack of language skills, (2) personal insecurities, (3) judgment of others, and (4) negative influences on performance and being. Students are recommended to work on their problems related to English language skills and make ways to improve such as through practicing, listening open-mindedly to constructive criticism, and building self-esteem. College teachers, meanwhile, are advised to foster a psychologically safe atmosphere where mistakes are seen as a learning opportunity, refrain from using deprecating comments to students, and undertake planned and meaningful class sessions.